Effect of soil nutrient management and land configuration on rhizospheric microbial diversity under cotton (Gossypium spp.)-wheat (Triticum aestivum) cropping system in semi-arid region - YADAV, RAJNI; GOYAL, V; BHARDWAJ, K K; KUMAR, RAKESH; RANI, MANU; DEVI, SONIA (The Indian Journal of Agricultural Sciences, 2024)
Microbial diversities in the vicinity of root rhizosphere play a crucial role in promoting plant and soil ecosystem health and productivity. They have great potential as key indicators of soil health in agro-ecosystems enhancing the availability of nutrients. Therefore, a study was carried out during 2019–20 and 2020–21 at research farm of Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to investigate the rhizospheric microbial diversities under cotton (Gossypium spp.)-wheat (Triticum aestivum L.) cropping system as affected by land configuration and nutrient management. Experiment consisted of 5 nutrient treatments replicated thrice and two land configurations, viz. raised bed (RB) and flatbed (FB) planned in factorial randomized block design (RBD). The results of experiment under RB revealed that farmyard manure (FYM) and FYM with biofertilizer and cow urine formulation (FYM + Org) showed the highest bacterial, fungal, phosphate solubilizing bacteria, azotobacter and actinomycetes population (6.92 to 7.51, 24.63 to 26.80, 7.61 to 7.68, 8.74 to 9.15,7.27 to 7.66 cfu/g soil, respectively). The decrease in microbial diversity was observed under inorganic fertilizer application through soil test crop response approach with targeted yield of 5.5 and 2.8 mg/ha (STCR5.5/2.8) and 6.0 and 3.2 mg/ha (STCR6.0/3.2) and control for cotton and wheat, respectively. Higher microbial population and soil organic carbon was found in RB compared to FB. The STCR5.5/2.8 and STCR6.0/3.2 recorded highest cotton and wheat yield followed by FYM and FYM+Org and least in control under cotton-wheat system. Thus, the study suggests that RB planting with an addition of manures along with biofertilizer and cow urine formulation could be a sustainable and feasible practice through enhanced microbial population raising soil fertility leading to increase the crop yields under semi-arid regions.